Strategy to Improve Learning Interest to Read Al-Quran at Al-Hidayah Al-Quran Learning Center, Morang Village, as Religious Character Education - Siska Agustina; M. A. Ghozali M. A. Ghozali; S. B. Panggali S. B. Panggali (Universitas Negeri Padang, 2022)
This article discusses learning strategies in reading Quran in Quran Learning Center. Quran Learning Center is a non-formal institution aimed as a place for children to learn how to read Quran which requires strategies. Reading Quran with fine and fluent must conform with the tajweed. This form of Islamic education was created with the aim on helping children to read the Qur'an when in formal schools they lack of exposed and lack of Islamic religious education teacher competence. Therefore, students are less facilitated in religious education. Al-Hidayah Quran Learning Center is located in Morang Village, Kare District, Madiun Regency. The objective of this research was to investigate strategies used by tutors in maintain learning interest of students in Al-Hidayah Quran Learning Center. This is a qualitative study using in-depth interview located at Morang Village, Kare District, Madiun Regency. The results showed that strategies used by tutors in maintain the learning interest of students in Al-Hidayah Quran Learning Center were Yanbu’a and Tartil method